Perbandingan Formulasi Tindak Pidana Judi Dalam Kitab Undang-Undang Hukum Pidana Di Indonesia Dengan Hukum Islam - Sari, Wulan Kartika; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The Arrangements on Gambling are governed by Article 303 of the Criminal Code and Article 303 bis of the Criminal Code jo. Law of the Republic of Indonesia Number 7 Year 1974 regarding Gambling Control. The purpose of writing this thesis that is to know the setting of gambling, weaknesses and advantages of gambling arrangements in the Book of Criminal Law in Indonesia and in Islamic Law.The research methods in this research, First, the type of research is normative law and descriptive analysis. Second, data sources are supported by primary data sources, secondary data, and tertiary data. Third, data collection techniques used are literature review or documentary study. After the data collected then analyzed qualitatively, and draw conclusions with the deductive thinking method of analyzing the problem from the general shape to the special form.From the results of this study that the authors do can be concluded. The setting of gambling is not based on the philosophical, sociological and juridical values of Indonesian society. The Criminal Justice Code only specifies that what is meant by gambling whereas in Islamic Law the criminal act of gambling is subject to ta'zir punishment.Keywords: Arrangement-Gambling-Islamic Law.